Factors Affecting Processed Sago Production in Pemakuan Village Sungai Tabuk Subdistrict - Sari, Irna; Jumriani, Jumriani; Ilhami, M. Ridha; Syarifuddin, Syarifuddin; Nur'aini, Fatwa (The Kalimantan Social Studies Journal, 2026)
The village of Pemakuan has been producing sago for many years, but recently, income from sago production has declined due to land conversion, as occasional shortages of sago raw materials have disrupted the sago processing production process. When sago raw materials are scarce, sago processing production also becomes disrupted. The effect is that the production process stops, resulting in no products being produced. The objective of this study is to describe the production of processed sago porridge. This study employs a qualitative approach and descriptive methods. The research findings indicate: Sago processing production in Pemakuan Village depends on several key factors, namely raw materials, labor, capital, and technology. 1) Raw materials are crucial, with sago as the primary material. It is sourced from local factories, and its availability can impact production. The price of sago raw materials is Rp 3,500 per kilogram. 2) Labor, particularly local residents, plays a vital role in production, as this industry provides employment opportunities. 3) Capital, whether in the form of money or goods, is essential for various aspects of production, from raw materials to employee wages. 4) Sago processing technology still relies on simple tools and basic equipment. Based on the research conducted, it was concluded that Pemakuan Village is known as the center of sago production in Sungai Tabuk Subdistrict, with many people involved in sago processing as their livelihood.